Addressing the issue of equity in health care provision during the transition period in Bulgaria - Markova, NK (2008)
The collapse of the communist regimes in Central and Eastern Europe in 1989-1990 heralded the beginning of an economic transition from central planning to market economies. The subsequent period was marked by malfunctioning of these countries’ social sectors, including their health care systems, raising serious issues of equity. This thesis examines the impact of the transition period and the introduction of social insurance on equity in health care provision in Bulgaria. Equity in health care is investigated with respect to function - i.e. financing (according to ability to pay) and delivery (according to need) - and outcomes - i.e. health status, income inequality and poverty. Differences in health, health care financing and delivery are explored by income, education, ethnic, employment, marital status, age and sex groups. Furthermore, the thesis outlines the impact of health care provision, in particular social insurance, on poverty and health inequalities. The thesis employs empirical analysis based on household data. Its methodology includes concentration and decomposition analysis, and provides new ways of modelling health care financing and delivery, as well as the link between health and health care delivery. The thesis concludes that social insurance does not provide a uniform means of improving equity and that the root cause of the problem lies in the large proportion of out-of-pocket payments and the rather limited size of the health insurance sector. Inequity in health care provision leads to poverty and untreated illness. The data suggests that there are differences between socio-economic groups as regards their likelihood to seek treatment for their ill health, which result in differences in their health status. The social factors that have impacted the most on health are low education and low income.